Inmigrants caregivers: emotional labor - Montserrat Ruiz López; Manuel Moreno Preciado (Universidad de Alicante, 2013)
The changes in demographic, economic, socio-cultural and health foster the emergence of a new set of caregivers: the hired caregiver, covered generally by immigrant women. This article is a study that aims to inquire into this new reality, focusing mainly on knowing the experiences and emotions of immigrant careers in relation to people and their environment maintained. The study, a qualitative research, collected through direct testimony of caregivers, which is their lived experiences, that is, the stories of a difficult and complex context, where it crosses a double need for affection: on one hand, the one of those suffering bereavement of immigration, by the distancing of their own family, by the harshness and precariousness of their migrant status and on the other hand, those who in old age, beyond physical dependence, suffer from loneliness. It demonstrates the emotional and relational nature of care and the positive contributions of these immigrant women to a situation characteristic of global societies, and with aging populations.